2016
DOI: 10.5312/wjo.v7.i6.376
|View full text |Cite
|
Sign up to set email alerts
|

Joint arthroplasty Perioperative Surgical Home: Impact of patient characteristics on postoperative outcomes

Abstract: AIM:To determine the impact of different characteristics on postoperative outcomes for patients in a joint arthroplasty Perioperative Surgical Home (PSH) program. METHODS:A retrospective review was performed for patients enrolled in a joint arthroplasty PSH program who had undergone primary total hip arthroplasty (THA) and total knee arthroplasty (TKA). Patients were preoperatively stratified based on specific procedure performed, age, gender, body mass index (BMI), American Society of Anesthesiologists Physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 32 publications
(38 reference statements)
1
2
0
Order By: Relevance
“…In our study, we did not find any difference in age and sex distribution between the two groups. Similar to our findings, two retrospective studies on total knee and hip arthroplasties also did not find any differences in age and sex distributions among the discharge destination groups 15 , 23) . Like most of the previous studies, our study revealed that among the patients with extended hospital stay, more were discharged to an ECF than to home.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, we did not find any difference in age and sex distribution between the two groups. Similar to our findings, two retrospective studies on total knee and hip arthroplasties also did not find any differences in age and sex distributions among the discharge destination groups 15 , 23) . Like most of the previous studies, our study revealed that among the patients with extended hospital stay, more were discharged to an ECF than to home.…”
Section: Discussionsupporting
confidence: 91%
“…A novel form of defined clinical pathway, called a Perioperative Surgical Home (PSH), has recently been described and implemented as a patient-centered model to improve healthcare delivery and reduce cost [31][32][33][34]. The PSH is a multidisciplinary rapid recovery pathway comanaged by orthopedic and anesthesia services.…”
Section: Cost Containmentmentioning
confidence: 99%
“…Their group found an increased ASA score was the only factor that contributed to an increased LOS and there was a higher readmission rate for these patients. There was no correlation with age, gender, procedure, or Charlson comorbidiy index (CCI) [30].…”
Section: Dischargementioning
confidence: 94%